Factors Influencing the Employee Job Satisfaction and Organizational Commitment: A Study of Selected Commercial Banks in Bangladesh - Kabir, ANM Jahangir (Asian Business Review, 2018)
This article strives to determine the most influential factors giving rise to employee job satisfaction and organizational commitment in the commercial banks of Bangladesh. Accordingly, the study aims at exploring the extent to which these employees are committed to their organizations and satisfied with different dimensions of their jobs.  This study was conducted   on the employees of commercial banks of Bangladesh. Out of the 300 survey questionnaires distributed among the respondents, 285 statistically usable questionnaires were received. A stepwise descriptive statistic, multiple regression analysis and one –way-ANOVA were used to confirm the research hypotheses.  The findings of the study indicated that reward and recognition, authority and feedback are highly influential factors influencing job satisfaction. Authority and feedback for affective commitment, work and working environment for continuance commitment and supervisor, and supervision for normative commitment have been found to be the most influential factors.
Keywords: Job satisfaction; Organizational commitment; Affective commitment; Continuance Commitment; Normative Commitment